2008
DOI: 10.1590/s0004-282x2008000300007
|View full text |Cite
|
Sign up to set email alerts
|

Role of physical activity on the maintenance of cognition and activities of daily living in elderly with Alzheimer's disease

Abstract: -Background:The practice of physical activities has proved to be an efficient strategy in the improvement of independency and cognitive functions in the elderly with Alzheimer's disease (AD). Objective: To evaluate the relation between the practice of physical activity, cognition and activities of daily living (ADL) of patients with AD. Method: The cognitive and physical aspects and ADL were evaluated of 37 elders (19 normal controls, 11 sedentary with AD and 7 active with AD). Results: The variable that best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
13

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 21 publications
(28 reference statements)
1
20
0
13
Order By: Relevance
“…The beneficial effect of regular physical exercise on the cognitive function may be associated to a good performance of the functional capacity. There are consistent data from studies which show positive effects on the balance and fall risk after physical exercise in patients with dementia, including AD 3,4,7,10,11 . In our study, we have also found positive results on the balance and fall risk.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The beneficial effect of regular physical exercise on the cognitive function may be associated to a good performance of the functional capacity. There are consistent data from studies which show positive effects on the balance and fall risk after physical exercise in patients with dementia, including AD 3,4,7,10,11 . In our study, we have also found positive results on the balance and fall risk.…”
Section: Discussionmentioning
confidence: 66%
“…Compared to sedentary people, the individuals who practice physical exercises present a lower chance of developing dementia (28%) and AD (45%) 3 . Our laboratory has observed a positive correlation between improvement in activities of daily living (ADL) and in the overall cognitive state among people with dementia who still have an active lifestyle 4 . Moreover, there is increasing evidence to support an inverse relationship between cardiorespiratory fitness and brain atrophy in the earliest clinical stages of AD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Same, Heyn et al, (2003) and Coelho et al (2009) have shown physical activity in older that adults with Alzheimer's disease can contribute positively by attenuating decline in cognitive function. However, most studies involving physical activity and Alzheimer disease have used general or aerobic training protocols (Arcoverde et al, 2008;Hernandez et al, 2010). Thereafter, Smith et al (2013) and Rolland et al (2000) showed that endurance exercise, walking or cycle ergometer, improved overall cognitive functions assessed by the MMSE and memory capacity as a main factor for the recognition of the level of Alzheimer's disease in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Neste estudo, mencionamos, como exemplo, os trabalhos realizados por Arcoverde et al (2008) e Sachs et al (2009).…”
Section: Introductionunclassified